PEREMPUAN DAN PENGEMBANGAN DESA WISATA KULINER PASAR DHOPLANG SLOGOHIMO - Putri, Riza Antika; Hermawan, Yosafat (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study aims to examine the role of women in the development of the culinary tourism village of Pasar Dhoplang located in Pandan Village, Slogohimo District, Wonogiri Regency. Pasar Dhoplang is one form of initiation from the women's community through Dasawisma Mawar Melati to form economic activities to improve the economy of the Dusun Kembar household. This descriptive qualitative study analyzes data systematically to draw conclusions. Data collection methods are primary data and secondary data such as interviews, observations, and documentation to obtain appropriate data. This study shows that the development of women in tourism development has a strategic role related to the flexible role of women in the domestic sphere, as well as being able to play a role in the management structure of Dhoplang Market. The application of women's roles through the triple rule outlined by Caroline Moser, namely reproductive roles, productive roles, and community roles. Through the involvement of women's active roles in the management of Pasar Dhoplang, it becomes an important factor in supporting the development of traditional Javanese culinary tourism villages. This study also examines the obstacles faced by women in the development of Pasar Dhoplang such as land ownership, inequality of participation within the village scope, and limited land in Pasar Dhoplang which hinders the empowerment of women in Pandan Village as a whole. Thus, the results of this study indicate that in developing regional tourism, there needs to be support from the role of women in its management structure in order to have an impact on improving the household economy.